Evolução paisagística: uso do solo no município de Palmelo(GO) - 2000 - 2016 - (:unkn) unknown (Universidade Federal de Goiás, 2017)
The Cerrado Biome region has been undergoing an intense process of occupation, structuring of development policies and government investments since the 1950s. Since then, unsustainable exploitation has been expanding, causing several social and environmental impacts. Considering the process of degradation of the Cerrado, it should be noted that agricultural activities pose one of the greatest environmental threats due to the inadequate use of natural resources that lead to severe environmental degradation through the destruction of habitats and imminently useful species. The landscape aspects of the Cerrado are described in order to understand the characterization of vegetation, soils, climate, lithological aspects and geomorphology, specifically in the area of the Municipality of Palmelo (GO), located in the Southeast Goiano, inserted in the Southern Mesoregion Goiana and Microregion of Pires do Rio. The present work studies the Cerrado Biome and its main characteristics, since it plays a fundamental function for the balance of the other Biomes of Brazil, analyzing the dynamics influencing landscape evolution and the main forms of use and occupation of the in the municipality of Palmelo (GO). As for the methodological aspects, the research was based on mechanisms used in the theoretical and documentary field in order to perform the satellite image analysis to obtain information about the respective classes of use, which guided the field research, composed by the survey of the practices in the landscape evolution in the researched area. In this way, it diagnosed the significant suppression in areas of primary vegetation remnants, which loses space for other classes of use, such as cultivated pastures, planting of crops and poultry, which together total 75.12%, while only 16, 33% of the native vegetation is preserved. There is also an exorbitant use of water resources in poultry farms, by means of harvesting in deep wells that do not receive supervision by the competent agencies. In this way, it is necessary to subsidize, elaborate and execute methodologies that allow and reconcile landscape conservation with economic development.
Landscape evolution: use of the soil in the municipality of Palmelo (GO)
Keywords: Cerrado; Uso do solo; Evolução paisagística; Palmelo (GO); Cerrado; Use of the soil; Landscape evolution; Palmelo (GO); GEOCIENCIAS::GEOGRAFIA FISICA